The Effectiveness of the Use of ProProfs Digital Media on the Interest and Learning Outcomes of Islamic Religious Education for Junior High School Students - Nur Izzah; Nur Fakhrunnisaa; Khaerunnisa (South Sulawesi Education Development (SSED), 2026)
This research is motivated by low student interest and learning outcomes in Islamic Religious Education among grade VII students at SMP Negeri 5 Palopo, due to limited variety in learning and minimal use of digital media. This study aims to determine the effectiveness of ProProfs digital media in increasing students' interest and learning outcomes. The method used is quantitative, with a quasi-experimental pretest-posttest control group design. The sample consisted of two classes, namely the experimental and control classes, each comprising 21 students. Data collection techniques use observation, questionnaires, and tests. The results showed that students' interest in learning in the experimental class increased from 37.38% to 82.91%, while learning outcomes improved from an average score of 32.14 to 84.57. The hypothesis test showed a p-value < 0.05, so ProProfs media was declared effective in increasing students' interest and learning outcomes.